Standing by the wall : the collected Slough House novellas - Herron, Mick (Herron, Mick. Slough house., 2022)
"Espionage. Subterfuge. Blackmail. Mystery. Humor. Revenge. Failure. Success. All this and more in a tight package of five novellas by Mick Herron, author of the Slough House novels, the books that inspired Slow Horses from Apple TV+. For fans new and old, Standing by the Wall is both an excellent introduction to the extended literary universe of Mick Herron and an immersive expansion of said universe. Meet more bad spies and even worse detectives. Race against time to solve mysteries with no easy conclusion. And understand the origins of Jackson Lamb, Mick Herron's most enigmatic, controversial character. The five novellas in this collection-including one never-before-published look into the past of Slough House-show Mick Herron as the undisputed master of the modern spy narrative, staying true to the classics of the genre while updating the form for a whole new generation of espionage readers"--